PERENCANAAN TEBAL PERKERASAN LENTUR JALAN DENGAN METODE AASHTO 1993 - Idwan, Idwan; Abdullah, Rudi (PARADIGM : Journal Of Multidisciplinary Research and Innovation, 2023)
Planning Thickness of Road Flexible Pavement Using the Aashto 93' Method. From the background that has been stated, it is necessary to formulate a problem that can be drawn is How to plan pavement thickness by paying attention to pavement design factors AASHTO 1993 method. The purpose of this study was to plan the thickness of flexible pavement using the AASHTO 1993 method on the Education Road, Raha III Village, Katobu District, Muna Regency. Based on the results of the analysis, it can be concluded that in planning the thickness of flexible pavement using the AASHTO 1993 method, several parameters are needed, such as average daily traffic, design age, traffic development, lane and direction distribution factors and standard deviation. From the results of calculations using the AASHTO 1993 method with parameter values that have been obtained from the research results, the thickness of each pavement layer is obtained as follows: 1). Surface Layer (Lasbutag) = 4 cm. 2). Foundation layer (class A crushed stone) = 10 cm. 3). Lower Foundation Layer (Sitru/pitrun class A) = 6 cm.